The Use of ion Plasmaclsuter in Decreasing level of Fe in Clean Water - Tri Cahyono; Hari Rudijanto Indro Wardono; Asep Tata Gunawan (Jurnal Riset Kesehatan, 2014)
The purpose of this research describe the difference of decreasing level of Fe between the well water before and after ionized. This type of research is pre-experimental, with design and pre-test post-test group design. The well water is collected in drum of 200 liter and given a cover. With the pump, water sprayed through a nozzle in a basin of aeration (control). The treatment group, using plasmacluster ion generator. Each replication three times. Data Analysis with One Sample Test and ANOVA. The measurement result  for the Fe content of the one nozzle control the average 0.617 mg / l, two nozzle 0.640 mg / l, three nozzle 0.639 mg / l and four nozzle 0.635 mg / l. Treatment group (ionization plasmacluster), the one nozzle average 0.571 mg / l, two nozzle 0.581 mg / l, three nozzle 0.573 mg / l and four nozzle 0.587 mg / l. Analized test with One Sample Test showed the significant difference (0.000 and 0.001 less than 0.05) with plasmacluster use of ionization in decreased levels of iron (Fe) and just well water with  using aeration. That were significant difference before (0.000) and after (0.001) uses plasmacluster ion in decreasing level of Fe well water (less than 0.05). The recomendation researcher  measured levels of early oxygen, the color before and after the ionization process.